Illuminativa - The Coalescence of Light and Craft Thinking - Ventling, Friedrich Derek (Auckland University of Technology, 2013)
This project constitutes a practice-led investigation of light as a metaphor for divine wisdom and how it might interact conceptually, physically and creatively with manual craft. The genesis of the project lies in Saint Bonaventure’s 13th Century work On the Reduction of the Arts to Theology. His treatise proposes a connective relationship between manual skill, sense perception, intellectual capacity and divine wisdom (as the source of all illumination). In this research, light is explored as form – as a connective agent, one that is interactive yet ephemeral, providing disclosure and exchange. Light itself is also the research tool. It is used to capture, develop and express a subjective interpretation of Bonaventure’s theory of illuminated connectivity. The resulting artefacts (combining analogue and digital techniques) and approaches to research propose a reconsideration of creative consciousness in contemporary graphic design practice.
Keywords: Illumination; Heuristics; Manual craft